ccfDNA analysis for the classification of adrenocortical adenomas - Xu, Mengjie; Tourigny, David S.; Lippert, Juliane; Crastin, Ana; Appenzeller, Silke; Asia, Miriam; Podstawka, Oskar; Smith, Gabrielle; Elhassan, Yasir S.; Skordilis, Kassiani; Prete, Alessandro; Ronchi, Cristina L. (Journal of endocrinological investigation, 2025)
Background Somatic alterations are commonly observed in adrenocortical adenomas including cortisol-producing (CPA) [overt Cushing syndrome (CS) or mild autonomous cortisol secretion (MACS)], aldosterone-producing (APA), and non-functioning (NFAT) tumors. We tested whether somatic variants could be detected in circulating cell-free DNA (ccfDNA) from patients with adenomas and potentially contribute to management strategies. Materials and methods We investigated 44 patients (17 CPA-MACS, 9 CPA-CS, 12 APA, and 6 NFAT). 23 healthy subjects (HS) served as controls. ccfDNA was extracted from blood samples and quantified with fluorimeter. Tumor DNA (T-DNA) was isolated from paraffin embedded tissue in 17/44 cases. Matched ccfDNA/T-DNA were sequenced using a customized panel including 32 genes. Leucocyte DNA was used to filter out germline variants. Results Patients with adenomas had higher total ccfDNA concentrations than HS [median 0.12 (IQR 0.05–0.19) vs. 0.05 (0.00-0.08) ng/µl, P < 0.001], with CPA-CS showing the highest ccfDNA levels [0.18 (0.05–0.47) ng/µl]. Within T-DNA, somatic variants were identified in 53% of adenomas: PRKACA in 2/7 CPA-CS, CTNNB1 in 3/5 CPA-MACS and 1/7 CPA-CS, KCNJ5 in 2/5 APA and CACNA1D in 1/5 APA. Somatic mutations were not detected in any of the investigated ccfDNA samples. Conclusions Total ccfDNA concentrations are higher in patients with CPA-CS. Despite the presence of somatic variants in half of tumor samples, we did not detect any at ccfDNA level. Therefore, this approach appears ineffective for pre-operative detection of genetic alterations.